HUBUNGAN PERILAKU MENYIKAT GIGI SERTA TINGKAT KEBERSIHAN GIGI DAN MULUT PADA IBU PKK BANJAR ADAT KAYUSUGIH KECAMATAN PUPUAN KABUPATEN TABANAN TAHUN 2019 - Ni Wayan Arini; Asep Arifin Senjaya; Ni Putu Puspa Dewi; Ni Ketut Ratmini (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2020)
Oral health is important for general bodily health and greatly influences the quality of life, in this case the functions of speech, mastication, and self-confidence. Bali Province is one of the provinces in Indonesia which has a higher prevalence of dental caries experience than the national prevalence. The health of a person or community is influenced by two main factors, namely: behavioral factors and non-behavioral factors. The purpose of this study was to determine the relationship between tooth brushing behavior and the level of dental and oral hygiene in PKK mothers in Banjar Adat Kayusugih, Pupuan District, Tabanan Regency in 2019. This type of cross sectional study, uses secondary data from Ni Putu Puspa Dewi research. Spearmen correlation test results between the variables of tooth brushing behavior with oral and dental hygiene obtained results of pipip: 0,000. The conclusion of the study there is a relationship between tooth brushing behavior with oral and dental hygiene as measured by OHI-S in PKK Banjat Adat Kayusugih, Pupuan Subdistrict, Tabanan Regency in 2019.